Antioxidant, Antimicrobial and Antidiarrhoeal Activity of Methanolic Extract of Rumex maritimus L. (Polygonaceae) - Md. Shafayat Hossain, A. H. M. Arifur Rashid, Md. Mahmudur Rahman, Samir Kumar Sadhu (Journal of Applied Pharmaceutical Science, 2015)
The aim of this current study was to evaluate phytochemistry along with pharmacological activities of the whole plant of Rumex maritimus L. (Family: Polygonaceae). Phytochemical analysis of the extract of R. maritimus indicates the presence of Reducing Sugar, Glycoside, Gum, Tannin and Alkaloid type compounds and the pharmacological attention of these compounds prompted us to check R. maritimus for possible anti-oxidant, antimicrobial and antidiarrheal activities in a dose dependent manner. The dried plants were subjected to successive extraction with methanol and the extract was used to investigate the activities. The extract of plants produced good diarrheal inhibition in castor oil induced diarrhea in mice (250mg/kg and 500mg/kg body weight) which was comparable to the standard drug Loperamide at the dose of 3 mg/kg of body weight. The alcoholic extract was showed anti-bacterial activity against the tested microorganisms (both gram positive as well as negative bacteria). This study reveals the potent anti-oxidant activity that is (IC50~80 µg/ml) to that of standard drug ascorbic acid (IC50 about ~7 µg/ml) in-vitro when tested in 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) scavenging method. The obtained results provide a support for the use of this plant in traditional medicine and its further investigation.
Keywords: R. maritimus, Polygonaceae, anti-oxidant, DPPH scavenging, antimicrobial and antidiarrhoeal activities.